2015
DOI: 10.1074/jbc.m114.618389
|View full text |Cite
|
Sign up to set email alerts
|

Solid-state NMR Reveals the Carbon-based Molecular Architecture of Cryptococcus neoformans Fungal Eumelanins in the Cell Wall

Abstract: Background: Melanin is a poorly understood fungal virulence factor. Results: 2D 13 C-13 C correlation solid-state nuclear magnetic resonance reveals the carbon-based molecular architecture of intact melanin pigment assemblies in Cryptococcus neoformans. Conclusion: Polysaccharide cell-wall components form a scaffold for layered deposition of aromatic-based pigment assemblies. Significance: Deciphering macromolecular interactions that drive melanin pigment assembly in fungal cell walls facilitates the developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
81
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(93 citation statements)
references
References 63 publications
5
81
0
3
Order By: Relevance
“…A monotonic curve was observed for the pelleted cellular material collected from C. neoformans cells grown in MM with L-DOPA (melanin granules and vesicles), but not for ∆LAC1,2 strain grown in MM with L-DOPA (L-DOPA aggregates and vesicles) nor for the fungal cells grown in MM lacking L-DOPA (vesicles) (Figure 4A). DLS also yields a dispersity index, which is a measure of the dispersion (or spread) in the estimated hydrodynamic sizes of colloidal particles in a solution (15,16). We observed that melanin granules had lower dispersity than autopolymerized L-DOPA ( Figure 4B).…”
Section: Resultsmentioning
confidence: 85%
See 4 more Smart Citations
“…A monotonic curve was observed for the pelleted cellular material collected from C. neoformans cells grown in MM with L-DOPA (melanin granules and vesicles), but not for ∆LAC1,2 strain grown in MM with L-DOPA (L-DOPA aggregates and vesicles) nor for the fungal cells grown in MM lacking L-DOPA (vesicles) (Figure 4A). DLS also yields a dispersity index, which is a measure of the dispersion (or spread) in the estimated hydrodynamic sizes of colloidal particles in a solution (15,16). We observed that melanin granules had lower dispersity than autopolymerized L-DOPA ( Figure 4B).…”
Section: Resultsmentioning
confidence: 85%
“…Prior studies have shown that the solid yeast-shaped particles lacking all internal structures designated as "melanin ghosts", are composed of smaller spherical structures ranging in diameter from 40 to 130 nm (21,49). We hypothesized that these particles were held together by non-pigment cellular components, a supposition supported by NMR studies showing that C. neoformans ghosts contain tightly associated lipid moieties and cellwall polysaccharides such as chitin (16,19). Since polysaccharides are typically susceptible to acid hydrolysis, we reasoned that prolonging the hydrochloric acid (HCl) incubation conducted during the melanin ghost isolation protocol would free the smaller spherical melanin particles for further analysis.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations